The transcription factors Scl and Lmo2 act together during development of the hemangioblast in zebrafish. - Patterson, L; Gering, M; Eckfeldt, C; Green, A; Verfaillie, C; Ekker, S; Patient, R (2007)
The transcription factors Scl and Lmo2 are crucial for development of all blood. An important early requirement for Scl in endothelial development has also been revealed recently in zebrafish embryos, supporting previous findings in scl(-/-) embryoid bodies. Scl depletion culminates most notably in failure of dorsal aorta formation, potentially revealing a role in the formation of hemogenic endothelium. We now present evidence that the requirements for Lmo2 in zebrafish embryos are essentially the same as for Scl. The expression of important hematopoietic regulators is lost, reduced, or delayed, panendothelial gene expression is down-regulated, and aorta-specific marker expression is lost. The close similarity of the phenotypes for Scl and Lmo2 suggest that they perform these early functions in hemangioblast development within a multiprotein complex, as shown for erythropoiesis. Consistent with this, we find that scl morphants cannot be rescued by a non-Lmo2-binding form of Scl but can be rescued by non-DNA-binding forms, suggesting tethering to target genes through DNA-binding partners linked via Lmo2. Interestingly, unlike other hematopoietic regulators, the Scl/Lmo2 complex does not appear to autoregulate, as neither gene's expression is affected by depletion of the other. Thus, expression of these critical regulators is dependent on continued expression of upstream regulators, which may include cell-extrinsic signals.